Health-care worker retention in post-conflict settings: a systematic literature review. Issue 1 (31st October 2022) - Lin, Tracy Kuo; Werner, Kalin; Kak, Mohini; Herbst, Christopher H
Abstract: Conflicts affect health-care systems not only during but also well beyond periods of violence and immediate crises by draining resources, destroying infrastructure and perpetrating human resource shortages. Improving health-care worker (HCW) retention is critical to limiting the strain placed on health systems already facing infrastructure and financial challenges. We reviewed the evidence on the retention of HCWs in fragile, conflict-affected and post-conflict settings and evaluated strategies and their likely success in improving retention and reducing attrition. We conducted a systematic review of studies, following PRISMA guidelines. Included studies (1) described a context that is post-conflict, conflict-affected or was transformed by war or a crisis; (2) examined the retention of HCWs; (3) were available in English, Spanish or French and (4) were published between 1 January 2000 and 25 April 2021. We identified 410 articles, of which 25 studies, representing 17 countries, met the inclusion criteria. Most of the studies (22 out of 25) used observational study designs and qualitative methods to conduct research. Three studies were literature reviews. This review observed four main themes: migration intention, return migration, work experiences and conditions of service and deployment policies. Using these themes, we identify a consolidated list of six push and pull factors contributing to HCW attrition in fragile, conflict-affected and post-conflict settings. The findings suggest that adopting policies that focus on improving financial incentives, providing professional development opportunities, establishing flexibility and identifying staff with strong community links may ameliorate workforce attrition.